Laptop security system / Mohamad Faizal Mohammed Shaffe and Muhamad Ikmal Rashidi - Rashidi, Muhamad Ikmal; Mohammed Shaffe, Mohamad Faiza (2015)
Laptop theft activity is often we hear. Nowadays, laptop has been a good target for thieves. It is because laptops are valuable, easy to resell, and have market. Therefore, laptop security system has always been a matter of concern among laptop user. Advancement in technology enables a new innovative method of laptop safety to be introducing into the market. Nowadays laptop security include of lock cable. It can be cut by using strong cutter and it needs other heavy object that cannot be removes to attach with it. The main objective of this project is to improve the security system of the laptop to become more effective and efficient. The system in this project is used to detect motion of theft activity. So the unwanted things can be avoided because this system will alarm the user before the thief can cut the lock cable. So the effectiveness of the security can be improved. This project title is Laptop Security System. This project works in a combination of microcontroller, PIR sensor as the input, then a buzzer and LED as the output. The system will trigger the alarm to alert the user if there is any movement or trial in optimum range to lift or move the laptop. It is similar to other security alarm system, but it is an application base on laptop security instead of home and vehicle security alarm system. Furthermore, this project will be expected to enhance the capability of the existing security system and it should be has good application value in future as well as reduce the statistic of stolen laptop. In the future, it should be improved the concept of this security to make more reliable towards an efficient security alarm system.